A Universal Framework for the Benefit-Risk Assessment of Medicines: Is This the Way Forward?. (January 2015) - Walker, Stuart; McAuslane, Neil; Liberti, Lawrence; Leong, James; Salek, Sam
A universal framework for the evaluation of the benefit-risk assessment of medicines during development by pharmaceutical companies and in the regulatory review by regulatory authorities is considered of value, as it would result in the systematic structured approach to support transparency in decision making. Several organizations have developed frameworks over the past few years, including those recommended by pharmaceutical companies such as the PhRMA BRAT (Pharmaceutical Research and Manufacturers of America Benefit-Risk Action Team) and the BRAIN (Benefit-Risk Assessment in New and Old Drugs) as well as frameworks advanced by regulatory agencies, including the FDA 5-step framework and the EMA PrOACT-URL. However, a review of the criteria—including logical soundness, comprehensiveness, acceptability of results, practicality, specificity and sensitivity, presentation (visualization), and scope proposed for the development of a universal framework—demonstrated that all these different frameworks described can be incorporated into UMBRA (Universal Methodology for Benefit-Risk Assessment).